The Effect of Increased Lodging Rates, Service Quality, and Facilities on Tourist Satisfaction and Loyalty During the Mandalika MotoGP - Akbar, Daffa Ayodya; Diswandi, Diswandi (International Journal of Economics Studies, 2025)
MotoGP Mandalika, a global event attracting domestic and international tourists, significantly impacts the hospitality industry. This study investigates how increased hotel rates during MotoGP Mandalika influence tourist satisfaction and loyalty. Utilizing a quantitative approach, data from 126 respondents staying in Mandalika hotels were analyzed through regression, descriptive statistics, and reliability tests. Results reveal that while higher rates correlate positively with perceived service quality and facilities, they do not significantly impact satisfaction. Facilities and service quality emerge as key drivers of both satisfaction and loyalty. The findings suggest the need for strategic management in pricing and service delivery during major events to balance industry goals and tourist expectations.